2004
DOI: 10.1111/j.1471-1842.2004.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic books in midwifery education: the student perspective

Abstract: The objectives of this paper are: (i) to illustrate the use of e-books by health studies students at a college of higher education; (ii) to provide a demonstration of how e-books may be facilitated by library and information services staff working across the health and academic sectors; (iii) to comment upon the experiences of health studies students, in using e-books. A focus group of 10 student midwives was used to gain insight into how e-books may be used in an academic context for health professionals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…14 Strategies identified in the literature for promoting the use of e-books include embedding them within online or virtual learning environments such as course websites or course management systems, user training for e-books, and direct promotion to faculty members. 15 …”
Section: Attitudes Towards E-booksmentioning
confidence: 99%
“…14 Strategies identified in the literature for promoting the use of e-books include embedding them within online or virtual learning environments such as course websites or course management systems, user training for e-books, and direct promotion to faculty members. 15 …”
Section: Attitudes Towards E-booksmentioning
confidence: 99%
“…Embedding the e-book content allows students to access directly the relevant content without having to read several chapters at a time. As previous studies have found, dipping in and out of content is the manner in which students successfully use eThe Embedded Textbook 12 books (Nicholas, et al, 2010;Christianson, M., 2005;Appleton, 2004). The initial time required to build the course BlackBoard site and embed the e-book links in each module proved time intensive for the authors.…”
Section: Discussionmentioning
confidence: 96%
“…While e-books may not be appropriate for all disciplines and university courses, studies have shown that the e-book model works especially well in the business disciplines (Buczynski, 2007;Jamali, Nicholas, & Rowlands, 2009;Nicholas, Rowlands, & Jamali, 2010;Dillon, 2001). Moreover, several studies indicate that students access and read e-books in the same manner as traditional textbooks; readers tend to "dip" in and out of sections of the text and digest information in chunked out text (Nicholas, et al, 2010;Christianson, M., 2005;Appleton, 2004). It is an easier transition for students to use an e-book like a textbook than for leisure reading.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The factors which benefit their use lies in saving time regarding acquisition and portability. However, their use can be affected given the attached elements (social networks, internet) which could distract the student 7 and be detrimental for their reading comprehension 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has described the disadvantages such as higher consumption of time 7 , difficulty in use 7 and many more distracting elements in the reading process 8 .…”
Section: Introductionmentioning
confidence: 99%